MicroRNA Involvement in Signaling Pathways During Viral Infection - Barbu, Madalina Gabriela; Condrat, Carmen Elena; Thompson, Dana Claudia; Bugnar, Oana Larisa; Cretoiu, Dragos; Toader, Oana Daniela; Suciu, Nicolae; Voinea, Silviu Cristian (Frontiers in Cell and Developmental Biology, 2020)
The study of miRNAs started in 1993, when Lee et al. observed their involvement in the downregulation of a crucial protein known as LIN-14 in the nematode Caenorhabditis elegans. Since then, great progress has been made regarding research on microRNAs, which are now known to be involved in the regulation of various physiological and pathological processes in both animals and humans. One such example is represented by their interaction with various signaling pathways during viral infections. It has been observed that these pathogens can induce the up-/downregulation of various host miRNAs in order to elude the host’s immune system. In contrast, some miRNAs studied could have an antiviral effect, enabling the defense mechanisms to fight the infection or, at the very least, they could induce the pathogen to enter a latent state. At the same time, some viruses encode their own miRNAs, which could further modulate the host’s signaling pathways, thus favoring the survival and replication of the virus. The goal of this extensive literature review was to present how miRNAs are involved in the regulation of various signaling pathways in some of the most important and well-studied human viral infections. Further on, knowing which miRNAs are involved in various viral infections and what role they play could aid in the development of antiviral therapeutic agents for certain diseases that do not have a definitive cure in the present. The clinical applications of miRNAs are extremely important, as miRNAs targeted inhibition may have substantial therapeutic impact. Inhibition of miRNAs can be achieved through many different methods, but chemically modified antisense oligonucleotides have shown the most prominent effects. Though scientists are far from completely understanding all the molecular mechanisms behind the complex cross-talks between miRNA pathways and viral infections, the general knowledge is increasing on the different roles played by miRNAs during viral infections.